Implications of genetic variation in the complement system in age-related macular degeneration. (September 2021) - de Jong, Sarah; Gagliardi, Giuliana; Garanto, Alejandro; de Breuk, Anita; Lechanteur, Yara T.E.; Katti, Suresh; van den Heuvel, Lambert P.; Volokhina, Elena B.; den Hollander, Anneke I.
Abstract: Age-related macular degeneration (AMD) is the main cause of vision loss among the elderly in the Western world. While AMD is a multifactorial disease, the complement system was identified as one of the main pathways contributing to disease risk. The strong link between the complement system and AMD was demonstrated by genetic associations, and by elevated complement activation in local eye tissue and in the systemic circulation of AMD patients. Several complement inhibitors have been and are being explored in clinical trials, but thus far with limited success, leaving the majority of AMD patients without treatment options to date. This indicates that there is still a gap of knowledge regarding the functional implications of the complement system in AMD pathogenesis and how to bring these towards clinical translation. Many different experimental set-ups and disease models have been used to study complement activation in vivo and in vitro, and recently emerging patient-derived induced pluripotent stem cells and genome-editing techniques open new opportunities to study AMD disease mechanisms and test new therapeutic strategies in the future. In this review we provide an extensive overview of methods employed to understand the molecular processes of complement activation in AMD pathogenesis. We discuss the findings, advantages and challenges of each approach and conclude with an outlook on how recent, exciting developments can fill in current knowledge gaps and can aid in the development of effective complement-targeting therapeutic strategies in AMD.